Translation, validation and psychometric properties of Bahasa Malaysia version of the Depression Anxiety and Stress Scales (DASS) - Musa, Ramli; Fadzil, Mohd Ariff; Zain, Zaini (ASEAN Federation of Psychiatry, 2007)
Background: Up to date, there are handful questionnaires that have been validated in Bahasa Malaysia (BM). This study aimed to translate the Depression Anxiety Stress Scales 21-item (DASS-21) and measure its psychometric properties. Objectives: To determine the construct validity and acceptability of the DASS, BM. Methods: Two forward and backward translations were done in BM in accordance to guideline, and its validation was determined by using confirmatory factor analysis. A total of 263 subjects were selected by systematic random sampling to represent Malaysian population for reliability and validity purposes. Results: The BM DASS-21 had very good Cronbach’s alpha values of .84, .74 and .79, respectively, for depression, anxiety and stress. In addition, it had good factor loading values for most items (.39 to .73). Correlations among scales were between .54 and .68. Conclusions: BM DASS-21 is correctly and adequately translated to Bahasa Malaysia with high psychometric properties. Further studies are required to support these findings.